BILINGUALISM AND COGNITIVE CONTROL: A PSYCHOLINGUISTIC THEORETICAL ANALYSIS - Rahmonova Zaynab Muzaffarovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article presents a theoretical psycholinguistic analysis of the relationship between bilingualism and cognitive control. The paper discusses language control, executive functions, and interference suppression in bilingual speakers based on modern scientific studies and theoretical approaches.